P16 Methylation was associated with the development, age, hepatic viruses infection of hepatocellular carcinoma, and p16 expression had a poor survival: A systematic meta-analysis (PRISMA). Issue 38 (September 2017) - Lv, Xueyou; Ye, Guoliang; Zhang, Xinjun; Huang, Tao
Abstract: Background: Loss of tumor suppressor gene p16 expression via promoter methylation has been reported in hepatocellular carcinoma (HCC). This meta-analysis was conducted to evaluate the correlation between p16 methylation and HCC. Additionally, we also analyzed the potential prognostic role of p16 methylation, expression or alteration-associated HCC. Methods: Online databases based on the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guideline were performed to analyze the role of p16 gene in HCC. The combined odds ratios (ORs) or hazard ratios (HRs) and their 95% confidence intervals (95% CIs) were summarized. Results: Final 3105 HCCs and 808 non-tumor controls (chronic hepatitis and liver cirrhosis) were performed in this meta-analysis. p16 promoter methylation in HCC was significantly higher than in chronic hepatitis and chronic hepatitis in tissue and blood samples. In addition, p16 promoter methylation was notably higher in patients >50 years' old than in patients aged <50 years, and it was higher in hepatitis B virus (HBV) or hepatitis C virus (HCV)-positive HCC than in hepatic viruses-negative HCC. However, p16 promoter methylation was not correlated with sex, cirrhosis, tumor differentiation, clinical stage. No association was found between p16 methylation or alteration and the prognosis of patients with HCC in overall survival (OS) and disease-free survival (DFS). Although p16 expression was significantly correlated with a poor prognosis in OS and DFS ( P  < .05) Conclusions: Our results indicate that p16 methylation was linked to the development, age, HBV, and HCV infection of HCC. p16 methylation or alteration was not associated with the prognosis, but p16 expression was linked to a poor survival. Abstract : Supplemental Digital Content is available in the text